Educar pela pesquisa : uma abordagem a partir da aplicação da história oral no ensino de História - Oliveira, Lauro Roberto Ferreira (2022)
This paper aims to demonstrate the use of research in the classroom as an educative principle that generates protagonism in the students, by applying the methodology of oral history as a process of production of historical knowledge over the final years of Basic Education. The intent is to encourage learning in the History curricular component, bringing the students closer to processes, practices and procedures of analysis and investigation. Specifically, it seeks to comprehend the usage of research as an educative and scientific principle in History teaching; to apply the oral history methodology in order to develop the protagonism of the students in the production of historical knowledge and elaborate a booklet with suggestions to the teacher about educating through research by using the oral history methodology to gather memories of oral expressions, by means of the use of interview techniques. The defended proposal was applied in a 9th grade class of Basic Education at the Alvina Rocha Municipal School, in the municipality of Seabra, state of Bahia, from the gathering of oral reports from residents of the Quilombola community of Agreste, Seabra, Bahia. The learners investigated historical, educational, identity and cultural aspects of the Quilombola community of Agreste. In the process, properly oriented, the students applied the research procedures of oral history, interviewed several collaborators and produced a historical document through the transcription of the interview. By applying the principles of analytic oral history, they sought to identify, compare, contextualize, interpret and analyze the documents produced, with the purpose of developing author skills by elaborating an article. From this experience, I present a booklet as a final product that contains suggestions to the teacher for the application of the principle of “educating through research” from the use of oral history methodology, with some thematic possibilities for research in Quilombola communities and cultures.